Repeated Assessment of Exploration and Novelty Seeking in the Human Behavioral Pattern Monitor in Bipolar Disorder Patients and Healthy Individuals - Minassian, Arpi (Public Library of Science, 2011)
BACKGROUND: Exploration and novelty seeking are cross-species adaptive behaviors that are dysregulated in bipolar disorder (BD) and are critical features of the illness. While these behaviors have been extensively quantified in animals, multivariate human paradigms of exploration are lacking. The human Behavioral Pattern Monitor (hBPM), a human version of the animal open field, identified a signature pattern of hyper-exploration in manic BD patients, but whether exploratory behavior changes with treatment is unknown. The objective of this study was to assess the sensitivity of the hBPM to changes in manic symptoms, a necessary step towards elucidating the neurobiology underlying BD. METHODOLOGY AND PRINCIPAL FINDINGS: Twelve acutely hospitalized manic BD subjects and 21 healthy volunteers were tested in the hBPM over three sessions; all subjects were retested one week after their first session and two weeks after their second session. Motor activity, spatial and entropic (degree of unpredictability) patterns of exploration, and interactions with novel objects were quantified. Manic BD patients demonstrated greater motor activity, extensive and more unpredictable patterns of exploration, and more object interactions than healthy volunteers during all three sessions. Exploration and novelty-seeking slightly decreased in manic BD subjects over the three sessions as their symptoms responded to treatment, but never to the level of healthy volunteers. Among healthy volunteers, exploration did not significantly decrease over time, and hBPM measures were highly correlated between sessions. CONCLUSIONS/SIGNIFICANCE: Manic BD patients showed a modest reduction in symptoms yet still demonstrated hyper-exploration and novelty seeking in the hBPM, suggesting that these illness features may be enduring characteristics of BD. Furthermore, behavior in the hBPM is not subject to marked habituation effects. The hBPM can be reliably used in a repeated-measures design to characterize exploration and novelty seeking and, in parallel with animal studies, can contribute to developing treatments that target neuropsychiatric disease.